Gestational Alloimmune Liver Disease and Neonatal Hemochromatosis - Whitington, Peter F. (Seminars in Liver Disease, 2012)
Neonatal hemochromatosis (NH) is a clinical syndrome consisting of liver disease and pathologic siderosis of various extrahepatic tissues. NH is a form of secondary hemochromatosis in which severe fetal liver injury causes iron overload due to poor regulation of maternofetal iron flux. Gestational alloimmune liver disease (GALD) has been established as the cause of fetal liver injury resulting in nearly all cases of NH. In GALD, sensitization of some women to a fetal liver antigen results in development of specific antifetal liver IgG antibodies. When delivered to the fetal circulation these antibodies bind to the antigen and activate the terminal complement cascade resulting in hepatocyte injury and death. GALD may produce subacute and chronic fetal liver injury (congenital cirrhosis) typical of NH. It may also produce acute injury and acute liver failure of the fetus and newborn, often with no iron overload or siderosis.
Keywords: hemochromatosis; alloimmune; fetus